2018
DOI: 10.1007/s00025-018-0778-9
|View full text |Cite
|
Sign up to set email alerts
|

The Mixed Scalar Curvature of Almost-Product Metric-Affine Manifolds

Abstract: A pseudo-Riemannian manifold endowed with k > 2 orthogonal complementary distributions (called a Riemannian almost multi-product structure) appears in such topics as multiply warped products, the webs composed of several foliations, Dupin hypersurfaces and in studies of the curvature and Einstein equations. In this article, we consider the following two problems on the mixed scalar curvature of a Riemannian almost multi-product manifold with a linear connection: a) integral formulas and applications to splitti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
45
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(45 citation statements)
references
References 30 publications
0
45
0
Order By: Relevance
“…where the Ricci and scalar curvature are replaced by the mixed Ricci curvature Ric D , see (26), and its trace S D . In [25], we obtained the Euler-Lagrange equations for (4) with fixed g and variable T, see (30a-h), and examined critical contorsion tensors (and corresponding connections) in general and in distinguished classes of (1,2)-tensors. We have shown that T is critical for (4) with fixed g if and only if T obeys certain system of algebraic equations, however, unlike (3b), these equations heavily involve also the pseudo-Riemannian geometry of the distributions.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…where the Ricci and scalar curvature are replaced by the mixed Ricci curvature Ric D , see (26), and its trace S D . In [25], we obtained the Euler-Lagrange equations for (4) with fixed g and variable T, see (30a-h), and examined critical contorsion tensors (and corresponding connections) in general and in distinguished classes of (1,2)-tensors. We have shown that T is critical for (4) with fixed g if and only if T obeys certain system of algebraic equations, however, unlike (3b), these equations heavily involve also the pseudo-Riemannian geometry of the distributions.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, from [25] we know that if T is critical for the action (6), then D and D are totally umbilical with respect to ∇ -and to express this together with other conditions, a pair of equations like (3a,b) is not sufficient. Due to this fact, only in the special case of semi-symmetric connections we present the Euler-Lagrange equation in the form, which directly generalizes (5):…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…see [8,10,14], called the mixed scalar curvature, i.e., an averaged mixed sectional curvature. For instance, S mix = Ric(y, y) when n = 1 and a unit vector field y spans D ⊥ locally.…”
Section: Introductionmentioning
confidence: 99%